1982
DOI: 10.1002/ajpa.1330590107
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high altitude on the growth of children of high socioeconomic status in Bolivia

Abstract: The physical growth of middle to upper class children of primarily European ancestry attending the private French School in L Paz, Bolivia is described and analyzed to determine how high altitude affects growth in this group of children. The sample consists of 323 children, most between the ages of 8 and 14, who reside at altitudes between 3200 and 3600 meters, but who have spent different amounts of time at high altitude. Comparisons between children who differ in their exposure to high altitude, and comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
1
9

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 15 publications
(13 reference statements)
4
58
1
9
Order By: Relevance
“…Analyzing families, ethnicity, living place and altitudes of four Andean countries during -1998, Larrea (2002 found that the rate of growth retardation among children and adolescents was three times less in the best socioeconomic district than that in the worst socioeconomic district. The important contribution of poor socio-economic conditions to growth retardation at high altitude has been noted by studies in other populations (de Meer et al, 1995;Haas et al, 1982;Greksa 1986Greksa , 2006Stinson, 1982;Tripathy et al, 2007;Weitz et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Analyzing families, ethnicity, living place and altitudes of four Andean countries during -1998, Larrea (2002 found that the rate of growth retardation among children and adolescents was three times less in the best socioeconomic district than that in the worst socioeconomic district. The important contribution of poor socio-economic conditions to growth retardation at high altitude has been noted by studies in other populations (de Meer et al, 1995;Haas et al, 1982;Greksa 1986Greksa , 2006Stinson, 1982;Tripathy et al, 2007;Weitz et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Dado que las condiciones y estilo de vida son diferentes. Cabe resaltar que esas diferencias pueden deberse a la calidad en las dietas (Weinstein, 2007, Moseley, 2001, e inclusive pueden existir factores semejantes relacionados con los factores genéticos, nutricionales y socioeconómicos (Hoff, 1974, Malina 1974, Stinson, 1982, respectivamente.…”
Section: Discussionunclassified
“…En ese sentido, podemos indicar que el desarrollo del crecimiento depende del bagaje genético, nutricional, nivel socio-económico, dolencias, influencias ambientales, tendencia secular, actividad física (Nahas, et.al, 1992) y el nivel de altitud (Cossio-Bolaños, 2004, Stinson, 1982, Leonard, et.al, 1995, Lawrance, Greksa y Haas, 1982, Pawson, et.al, 2001). …”
Section: Introductionunclassified
“…The general growth patterns of these two populations have been previously described (Stinson, 1980(Stinson, , 1982. The rural children are of Aymara ancestry, born and raised in the northern altiplano of Bolivia, with parents who were born and raised in the northern Bolivian altiplano.…”
Section: Methodsmentioning
confidence: 97%